The natural history of protrusio acetabuli in Marfan syndrome and other hereditary connective tissue disorders: a 10-year follow-up CT study - Tordis Böker; Eva Kirkhus; Are Hugo Pripp; Svend Rand-Hendriksen; Benedicte Paus; Hans-Jørgen Smith; Rigmor Lundby (Orphanet Journal of Rare Diseases)
Abstract Objectives To explore the natural history of protrusio acetabuli (PA) in adults with Marfan syndrome (MFS) via a prospective 10-year follow-up study. Methods 2014 through 2015, 62 of 87 survivors from a nationwide cross-sectional study of 105 adults with presumed MFS were re-examined. At follow-up, MFS was diagnosed in 46 participants, and other hereditary connective tissue disorders in 12 participants. As in the baseline study, matched hospital controls were collected for comparison. CT images were obtained of the hips. PA was evaluated quantitatively and qualitatively. Measurements were performed according to the circle-wall distance method. The data was analysed with paired t test, and McNemar’s test. A receiver operating characteristic (ROC) curve was constructed for the circle-wall distance. Results There was no increase in the number of hips diagnosed with PA or in the circle-wall distance. PA was diagnosed in 58 of 87 hips in patients with MFS and in 71 of 111 hips in all patients with hereditary connective tissue disorders. Significantly more patients with MFS than controls had PA. Conclusion The prevalence and degree of PA remained unchanged after 10 years. The circle-wall distance seems to have a good ability to discriminate between individuals with MFS and individuals without any known connective tissue disorder. Suggested cutoff level for the circle-wall distance: 2 mm. Clinical relevance PA might be suggestive of a hereditary connective tissue disorder but does not develop or increase in adulthood. CT seems to have high sensitivity for PA and might be useful in a diagnostic process.